Amendment of biosolids with waste materials and lime: Effect on geoenvironmental properties and leachate production. (December 2015) - Kayser, Claudia; Larkin, Tam; Singhal, Naresh
Highlights: Waste amended biosolids were tested under simulated field conditions. Lime amended biosolids showed higher strength and stiffness under pressure. Strength increase was related to CaCO3 formation. Under typical field stresses large volumes of leachate production occurred. Metals in leachate were within NZ regulatory requirements for Class A landfills. Abstract: Residuals from wastewater treatment operations (biosolids) were mixed with lime, fly ash, lime kiln dust, or two smelter slags to assess their efficacy as potential stabilisation agents by assessing their effects on the shear strength, compressibility, and solids content of mixtures. In addition, the minerals formed and leachate produced during stabilisation were determined. Tests were performed to explore the change of the geoenvironmental properties of the amended biosolids, while under pressure, at different scales using laboratory, pilot and field scale tests. The settlement characteristics of the amended biosolids under a range of applied pressures were determined using a consolidometer. All amended biosolids mixtures showed higher strength than the unamended biosolids, with mixtures containing a combination of 20% fly ash and 20% lime giving the highest (up to eightfold) increase in strength, and that with lime kiln dust and the smelter slags showing the lowest (up to twofold). The biosolids mixtures with only lime gave the second highest increase in strength (up to fourfold), but produced the largest amount of leachate, with higher level of dissolved calcium. The increase in strength correlated with availability of calcium oxide in the mixtures which lead to calcium carbonate formation, accompanied with higher leachate production and settlement during consolidation. Copper, nickel and zinc concentrations increased with alkaline additives and corresponded to higher pH and DOC levels. Nonetheless, concentrations were within the New Zealand regulatory limits for Class A landfills.